Comparison of deacclimation and reacclimation of silver birch, Norway spruce and Scots pine seedlings during winter warm and cold spells in Nordic boreal conditions - Luoranen, Jaana; Kivimäenpää, Minna; Riikonen, Johanna (Springer Nature, 2024)
Climate change means that in many areas in boreal region, the duration and thickness of the winter snow cover is decreasing. Young seedlings are exposed to fluctuating winter temperatures in the absence of protecting snow cover. Responses to winter warm and cold spells were studied with Scots pine (Pinus sylvestris L.), silver birch (Betula pendula Roth.), and Norway spruce (Picea abies (L.) Karts.) container seedlings in Finland. The frost hardiness of whole seedlings and buds was determined for seedlings sampled directly from outdoor overwintering conditions, after 7-day deacclimation (+5 °C; +7 °C in late March) and deacclimation combined with 7-day reacclimation ( − 7 °C) treatments between January and late March. The frost hardiness of buds and whole seedlings in Scots pine was between  − 40 and  − 30 °C from January to early March. Norway spruces tolerated at least  − 50 °C in midwinter, but their frost hardiness in outdoor conditions decreased more rapidly in March than that of Scots pines. Silver birch tolerated  − 30 °C in February. During simulated warm spells, the Scots pine and silver birch deacclimated without an ability to reacclimate during simulated cold spells. The buds and whole seedlings of Norway spruces also deacclimated, but they had some ability to reacclimate in February and early March, but not in late March. In Nordic boreal conditions, one-year-old Scots pines and silver birches respond strongly to fluctuating winter temperatures during snowless winters, whereas Norway spruces can tolerate typical winter temperatures in midwinter, but their frost hardiness may reduce during warm spells in March.
Keywords: pakkasenkestävyys; metsäkuusi; metsämänty; rauduskoivu; taimikasvatus